Problematika Korespondensi Resmi Bagi Pegawai Kantor Perpustakaan Arsip dan Dokumentasi Kabupaten Tanah Datar - Arlita, Roza; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
Problem in this paper is the problem of official correspondence to the staff of the Library Archives and Documentation Tanah Datar. The purpose of this paper to explain the first, official correspondence causes problems for the staff of the Library Archives and Documentation Tanah Datar and second, knowing the constraints and corresponding implementation efforts in the Office of Library Archives and DocumentationTanahDatar. Paper data collection techniques used are direct observation (observation) observations are used to determine the circumstances that occurred in the institution and interviews with the staff of the Library Archives and Documentation Tanah Datar used to determine employed work processes, as well as an interview with the head of the library section as well as some other staff to complete the data of scientific writing. Based on the analysis of factors can cause problems for employes correspondence Library Archives and Documentation Office of Tanah Datar is the importance of the correspondence to the individual as a means of communication, the organization as a means of employment and facilitate communication among employees and other agencies. Greatly impact the lack of training in an agency employee skills and discipline employees who make less than the employee's performance declined. The lack of wisdom of the leadership led to discipline difficult to apply to the employee. Constraints faced by the Office of Records and Documentation Tanah Datar in conducting correspondence are: first, the things that must be considered in the correspondence in the making of both the institution and outside the institution. Second,a common phenomenon in the world of correspondence. Third, knowledge is still lacking correspondence obtained by the employee due to lack of training and information. Fourth, the errors in correspondence practice is an employee who made a mistake letter to leaders and letters to other agencies. Keywords: techniques; observation; communication; conducting and correspondence